Chemigenetic Ca2+ indicators report elevated Ca2+ levels in endothelial Weibel-Palade bodies. - Julian Terglane; Nicole Mertes; Sarah Weischer; Thomas Zobel; Kai Johnsson; Volker Gerke (PLoS ONE)
Weibel-Palade bodies (WPB) are secretory organelles exclusively found in endothelial cells and among other cargo proteins, contain the hemostatic von-Willebrand factor (VWF). Stimulation of endothelial cells results in exocytosis of WPB and release of their cargo into the vascular lumen, where VWF unfurls into long strings of up to 1000 µm and recruits platelets to sites of vascular injury, thereby mediating a crucial step in the hemostatic response. The function of VWF is strongly correlated to its structure; in order to fulfill its task in the vascular lumen, VWF has to undergo a complex packing/processing after translation into the ER. ER, Golgi and WPB themselves provide a unique milieu for the maturation of VWF, which at the level of the Golgi consists of a low pH and elevated Ca2+ concentrations. WPB are also characterized by low luminal pH, but their Ca2+ content has not been addressed so far. Here, we employed a chemigenetic approach to circumvent the problems of Ca2+ imaging in an acidic environment and show that WPB indeed also harbor elevated Ca2+ concentrations. We also show that depletion of the Golgi resident Ca2+ pump ATP2C1 resulted in only a minor decrease of luminal Ca2+ in WPB suggesting additional mechanisms for Ca2+ uptake into the organelle.